Transformation of Conventional Archives into Digital at the Medical Faculty of the University X - Ramadhan, Alfitah Carellina; Wolor, Christian Wiradendi; Marsofiyati, Marsofiyati (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
Archiving is one of the office jobs that is experiencing digital transformation. Digital archives make it easy for employees to complete their work however, it does not rule out that digital archives have weaknesses that can reduce employee performance. The purpose of this study was to analyze the digital filing system used by the X University Faculty of Medicine, find out whether the system used was effective or not, and find out the weaknesses of the digital archiving system. The research method used in this research is descriptive qualitative with a case study approach. The results of this study indicate that digital archives help employees complete work more quickly and make it easier for employees to carry out administrative activities in agencies. However, behind that it is necessary to repair, improve and upgrade the system so that problems do not occur and can be used more optimally.